A Review on Cardiovascular Outcome Studies of Dipeptidyl Peptidase-4 Inhibitors - Khalse, Maneesha (Indian J Endocrinol Metab, 2018)
The U.S. Food and Drug Administration issued a guidance for pharmaceutical industry defining preapproval and postapproval requirements for the demonstration of cardiovascular (CV) safety for all new medications developed for glycemic management in type 2 diabetes. However, results published from the studies of dipeptidyl peptidase-4 (DPP-4) inhibitors are conflicting with regard to different CV endpoints. Upcoming CV outcome studies perhaps will be able to provide additional insights related to diabetes management and help to provide the answers to some of these concerns. This article provides a brief overview regarding how various CV safety evidence of DPP-4 inhibitor evolved over time that highlights possible implication in clinical practice and translates them into effective diabetes management.